Sulfated Alginate Hydrogels Prolong the Therapeutic Potential of MSC Spheroids by Sequestering the Secretome (Adv. Healthcare Mater. 21/2021). Issue 21 (3rd November 2021) - Gionet‐Gonzales, Marissa; Casella, Alena; Diloretto, Daphne; Ginnell, Clara; Griffin, Katherine H.; Bigot, Anne; Leach, J. Kent
Abstract : Mesenchymal Stromal Cells In article number 2101048 by J. Kent Leach and co‐workers, spheroids of mesenchymal stromal cells (MSCs) secrete high levels of relevant growth factors (GFs) for tissue regeneration. Sulfated alginate can sequester these GFs through ionic interactions, allowing increased therapeutic potency to invading cells. This paper investigates how MSC spheroidsecreted GFs are retained in sulfated alginate and their ability to influence cell function in vitro.